Recursive method for inversion of lower triangular matrix - Rami reddy, B (Journal of Experimental Sciences, 2012)
Algorithm for finding by recursion, the inverse of a lower triangular matrix of order n is developed, using its last row and the sub matrix obtained by deleting the last row and last column. In these algorithms the hitherto using double suffix notation for the entries of amatrix is replaced by single suffix notation. The necessary results are established.